Sodium hyaluronate gel microspheres, and preparation method and application thereof

CN121574435BActive Publication Date: 2026-10-13XIANGTAN SUMEI MEDICAL TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610112911.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-27
Publication Date
2026-10-13
Estimated Expiration
2046-01-27

AI Technical Summary

Technical Problem

然而,凝胶的降解时间也会因交联度的提高而一并提高,导致HA凝胶在短降解周期与高模量两个性质上无法兼得,限制了HA凝胶在短期硬质填充领域的应用(如组织工程修复支架、术后防黏连、关节填充等)

Benefits of technology

1、本发明提供的透明质酸钠凝胶微球依靠透明质酸自交联形成,催化交联反应使用的碳二亚胺衍生物或N-羟基琥珀酰亚胺衍生物完成催化后不与透明质酸钠以化学键连接,可通过清洗从产物中移除,降低交联剂的不良反应风险;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121574435B_ABST
    Figure CN121574435B_ABST
Patent Text Reader

Abstract

The application discloses a sodium hyaluronate gel microsphere and a preparation method and application thereof, and belongs to the field of biomedical materials. The application claims a sodium hyaluronate gel microsphere which is formed by self-crosslinking of hyaluronic acid, and the crosslinking bond is an ester bond; the swelling degree of the sodium hyaluronate gel microsphere ranges from 12.5 to 70.9, and the particle size ranges from 2.8 to 2000 mu m. The sodium hyaluronate gel microsphere is formed by self-crosslinking of hyaluronic acid, and after catalyzing the crosslinking reaction by using a carbodiimide derivative or an N-hydroxysuccinimide derivative, the sodium hyaluronate is not connected to the sodium hyaluronate by a chemical bond, can be removed from the product by cleaning, reduces the risk of adverse reactions of the crosslinking agent, can also take into account high modulus and fast degradation, and the spherical sodium hyaluronate gel product obtained is easy to inject and use, and is particularly suitable for being used as a short-term hard filling material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials, and relates to sodium hyaluronate gel, specifically to a sodium hyaluronate gel microsphere, its preparation method, and its application. Background Technology

[0002] Hyaluronic acid (HA) is a polymer composed of acetylglucosamine and glucuronic acid linked by alternating glycosidic bonds, and is often found in sodium salt form. HA is a polysaccharide naturally present in human connective tissue, possessing excellent biocompatibility, water retention, and viscoelasticity. It is widely used in the field of medical aesthetics, such as skin filling, soft tissue repair, and joint lubrication.

[0003] Non-crosslinked HA is easily degraded by HA enzymes in vivo and has low mechanical strength, limiting its application in long-lasting filling and shaping. Therefore, crosslinking agents are often used to form HA into a gel network, improving its degradation resistance and increasing gel mechanical properties (such as modulus). At the same time, among various HA gel morphologies, spherical particles are more favored due to their rounded appearance, lower tissue irritation, and lower rolling resistance (easier to inject).

[0004] There are various cross-linking agents available for cross-linked HA, such as DVS (divinyl sulfone, National Medical Device Registration Certificate No. 20203130096), BDDE (1,4-butanediol glycidyl ether, National Medical Device Registration Certificate No. 20193130257), lysine (National Medical Device Registration Certificate No. 20243131239), and PEG (polyethylene glycol, National Medical Device Registration Certificate No. 20253130825). With advancements in cross-linking technology, the safety of cross-linking agents themselves has continuously improved. However, as foreign substances, cross-linking agents always carry the risk of causing adverse reactions such as allergies.

[0005] Furthermore, cross-linked HA gels can have a higher modulus (achieving a hard filling effect) compared to uncross-linked HA gels, and the higher the degree of cross-linking, the higher the modulus. However, the degradation time of the gel also increases with the degree of cross-linking, meaning that HA gels cannot simultaneously achieve both a short degradation cycle and high modulus, thus limiting their application in short-term hard filling applications (such as tissue engineering repair scaffolds, postoperative anti-adhesion, joint filling, etc.).

[0006] To address the issues of crosslinking agent allergy risk and the inability to simultaneously achieve short degradation cycles and high modulus in existing HA gel microspheres, this invention is proposed. Summary of the Invention

[0007] The present invention aims to overcome the shortcomings of the prior art. The first objective is to provide a sodium hyaluronate gel microsphere, the second objective is to provide a method for preparing the sodium hyaluronate gel microsphere, and the third objective is to provide the application of the sodium hyaluronate gel microsphere in the preparation of medical filler materials.

[0008] The above-mentioned objective of this invention is achieved through the following technical solution: A sodium hyaluronate gel microsphere, wherein the sodium hyaluronate gel microsphere is formed by self-crosslinking of hyaluronic acid, and the crosslinking bond is an ester bond; the swelling degree of the sodium hyaluronate gel microsphere ranges from 12.5 to 70.9, and the particle size ranges from 2.8 to 2000 μm.

[0009] A method for preparing sodium hyaluronate gel microspheres as described above includes the following steps: Step S1: Dissolve hyaluronic acid or its salt and the catalyst in solvent A to obtain an aqueous solution; Step S2: Dissolve the thickener in solvent B to obtain an oil phase solution; Step S3: Mix the aqueous solution and the oil solution, and carry out suspension polymerization. The product is obtained after the reaction is completed. in: In step S1, the catalyst is composed of a carbodiimide derivative and an N-hydroxysuccinimide derivative; a repeating unit is defined as a group of glucuronic acid and acetylglucosamine in hyaluronic acid or its salts, and the molar ratio of the repeating unit in hyaluronic acid or its salts to the carbodiimide derivative and the N-hydroxysuccinimide derivative is 1:(0.3~1.5):(0.15~2.25); the solvent A is selected from one or more of water, physiological saline, and phosphate buffer; the molecular weight of the hyaluronic acid or its salts is 40 kDa~1000 kDa, and its concentration in the aqueous solution is 5~22 wt.%. In step S2, the thickener is selected from one or more of cellulose acetate butyrate, cellulose acetate propionate, ethyl cellulose, polymethyl methacrylate, polystyrene, and polyvinyl butyral; the solvent B is selected from organic solvents that are immiscible with water.

[0010] Preferably, in step S1, the carbodiimide derivative is selected from one or more of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N,N'-dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide, and N-cyclohexyl-N'-(2-morpholinoethyl)carbodiimide methanesulfonate.

[0011] Preferably, in step S1, the N-hydroxysuccinimide derivative is selected from one or more of N-hydroxysuccinimide, sodium N-hydroxythiosuccinimide, and N-hydroxysulfosuccinimide.

[0012] Preferably, in step S1, the pH range of the aqueous solution is 4.55 to 6.95.

[0013] Preferably, in step S2, solvent B is selected from one or more of butyl acetate, amyl acetate, hexyl acetate, butyl propionate, butyl butyrate, dimethyl carbonate, and diethyl carbonate.

[0014] Preferably, in step S2, the concentration of the thickener in the oil phase solution is 0.5 ~ 15 wt.%.

[0015] Preferably, in step S3, the volume ratio of the aqueous phase solution to the oil phase solution is 1:1 to 40.

[0016] Preferably, in step S3, the temperature of suspension polymerization is 10 ~ 90℃, the reaction time is 0.5 ~ 24 h, and the stirring speed is 200 ~ 1500 rpm.

[0017] Application of the above-mentioned sodium hyaluronate gel microspheres or sodium hyaluronate gel microspheres prepared by any of the above preparation methods in the preparation of medical filler materials.

[0018] Beneficial effects: 1. The sodium hyaluronate gel microspheres provided by the present invention are formed by the self-crosslinking of hyaluronic acid. The carbodiimide derivative or N-hydroxysuccinimide derivative used to catalyze the crosslinking reaction does not chemically bond with sodium hyaluronate after catalysis, and can be removed from the product by washing, thereby reducing the risk of adverse reactions of the crosslinking agent. 2. The hyaluronic acid in the sodium hyaluronate gel microspheres provided by the present invention is cross-linked through ester bonds. The gel modulus is significantly increased due to the increase in the degree of cross-linking, while the degradation cycle changes little. Thus, it can take into account both high modulus and fast degradation, and is particularly suitable as a short-term rigid filler material. 3. Compared with existing technologies (such as CN 111647193 A for obtaining sponge-like sodium hyaluronate gel), the preparation method of the present invention can obtain spherical sodium hyaluronate gel products through suspension polymerization. The rolling resistance between spherical particles is small, making it easy to inject and use.

[0019] The mechanism by which the beneficial effects are produced: 1. Mechanism by which cross-linked products reduce the risk of adverse reactions Carbodiimide derivatives and N-hydroxysuccinimide derivatives are a group of catalysts that can activate carboxyl groups. The glucuronic acid unit in HA contains a carboxyl group, which can be activated. Both glucuronic acid and acetylglucosamine contain hydroxyl groups. The activated carboxyl group can react with the hydroxyl group to form an ester bond, i.e., HA crosslinks with HA, without the need for an additional crosslinking agent. The specific chemical reaction is shown in the following formula (taking EDC / NHS as an example).

[0020] ; The ester bonds in cross-linked HA can be broken by hydrolysis, and the glycosidic bonds between glucuronic acid and acetylglucosamine in HA are also unaffected by the ester bonds and can still be hydrolyzed (or enzymatically hydrolyzed). No cross-linking agent fragments are released after degradation, therefore there are no safety risks associated with cross-linking agents. In contrast, the cross-linking agents used in existing publicly available technologies (such as BDDE) directly link to HA molecules during cross-linking, forming chemical bond structures such as HA-BDDE-HA, which cannot be removed by washing. This inevitably leads to the release of cross-linking agent molecules after the gel degrades in the human body, resulting in the risk of adverse reactions related to cross-linking agents.

[0021] 2. Mechanism that balances high modulus and rapid degradation Traditional cross-linking agents such as BDDE, DVS, and lysine cross-link HA gels use ether or amide bonds, which are highly resistant to hydrolysis. The small pore size of cross-linked HA gels prevents large protein molecules like HA enzymes from penetrating, causing the gel to degrade only from the surface. Therefore, both cross-link hydrolysis and HA enzymatic hydrolysis must be considered, with enzymatic hydrolysis being the rate-determining step in the overall gel degradation. As the degree of cross-linking increases, the gel's resistance to enzymatic hydrolysis significantly increases. In the in vivo environment where hydrolysis and enzymatic hydrolysis occur simultaneously, the overall degradation time of the gel increases significantly with the degree of cross-linking.

[0022] In contrast, the HA gel disclosed in this invention is cross-linked via ester bonds, which are easily hydrolyzed chemical bonds. Water molecules are smaller than the network pores of the gel, and all chemical bonds within the gel hydrolyze simultaneously upon contact with water. Therefore, hydrolysis is the rate-determining step in the overall gel degradation. Even by increasing the degree of cross-linking and the number of ester bonds (while simultaneously improving the mechanical properties of the gel), the degradation cycle of the gel is less correlated with the degree of cross-linking because the hydrolysis of ester bonds within the gel occurs simultaneously (water molecules can penetrate the gel network), rather than starting from the surface of the gel particles. Therefore, increasing the degree of cross-linking can significantly improve the gel's modulus without significantly increasing the degradation time, achieving a balance between rapid gel degradation and high modulus.

[0023] 3. Mechanism of obtaining spherical sodium hyaluronate gel via suspension polymerization Spherical particles have low rolling resistance and are easy to inject, while irregular particles, due to their protrusions and depressions, are difficult to inject. The disclosed technology (CN 111647193 A) tends to produce porous, foamed structures when synthesizing blocky HA gels. The inventors discovered that a small amount of isocyanate (a raw material for the synthesis of carbodiimide derivatives) inevitably remains during the production process of carbodiimide derivatives. Isocyanate reacts with water to produce carbon dioxide, thereby causing foaming and cross-linking of HA. This invention disperses the aqueous solution into micron-sized droplets, allowing carbon dioxide to easily diffuse and detach from the gel, forming dense, rounded, and non-porous cross-linked HA. Attached Figure Description

[0024] Figure 1 Optical microscope images of the product of Example 1 after reconstitution with physiological saline (A), the product of Example 1 after dry powder (B), and the product of Comparative Example 1 after reconstitution with physiological saline (C).

[0025] Figure 2 The results are the energy storage modulus test results of the products of Examples 1, 4, 6 and 7.

[0026] Figure 3 The infrared spectra of the product prepared in Example 7 and its raw materials are shown.

[0027] Figure 4 The particle size distribution diagrams are of the products prepared in Examples 7 to 10. Detailed Implementation

[0028] The substantive content of the present invention will be described in detail below with reference to specific embodiments. However, those skilled in the art should know that the scope of protection of the present invention should not be limited to these specific embodiments.

[0029] I. Preparation of sodium hyaluronate gel microspheres

[0030] Example 1: Step S1: Dissolve HA (hyaluronic acid, hereinafter the same) with a molecular weight of 100 kDa in deionized water to form a solution with a concentration of 10 wt.%. Adjust the pH to 4.8±0.05 with 0.1 M HCl / NaOH, and add EDC and NHS in the following ratio: HA repeating unit (one set of glucuronic acid and acetylglucosamine is recorded as one repeating unit): EDC (1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, hereinafter the same): NHS (N-hydroxysuccinimide, hereinafter the same) = 1:0.5:0.5 (molar ratio). Stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0031] Step S2: Dissolve cellulose acetate butyrate in butyl acetate to form a 5 wt.% solution as the oil phase.

[0032] Step S3: Under mechanical stirring at 10 ℃ and 1000 rpm, 50 mL of aqueous phase was added to 500 mL of oil phase, and the mixture was suspended and polymerized for 24 h. After the reaction was completed, the microspheres were collected by centrifugation, dialyzed against the oil phase solvent and anhydrous ethanol in sequence, and dried to obtain the product.

[0033] Example 2: Step S1: Dissolve HA with a molecular weight of 200 kDa in deionized water to form a solution with a concentration of 8 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:0.5:0.5 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0034] The other steps are the same as in Example 1.

[0035] Example 3: Step S1: Dissolve HA with a molecular weight of 500 kDa in deionized water to form a solution with a concentration of 5 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:0.5:0.5 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0036] The other steps are the same as in Example 1.

[0037] Example 4: Step S1: Dissolve HA with a molecular weight of 100 kDa in deionized water to form a solution with a concentration of 10 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:0.3:0.3 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0038] The other steps are the same as in Example 1.

[0039] Example 5: Step S1: Dissolve HA with a molecular weight of 1000 kDa in deionized water to form a solution with a concentration of 5 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:0.5:0.5 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0040] The other steps are the same as in Example 1.

[0041] Example 6: Step S1: Dissolve HA with a molecular weight of 100 kDa in deionized water to form a solution with a concentration of 10 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:1.0:1.0 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0042] The other steps are the same as in Example 1.

[0043] Example 7: Step S1: Dissolve HA with a molecular weight of 100 kDa in deionized water to form a solution with a concentration of 10 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:1.5:1.5 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0044] The other steps are the same as in Example 1.

[0045] Example 8: Step S1: Dissolve HA with a molecular weight of 40 kDa in physiological saline to form a solution with a concentration of 6 wt.%. Adjust the pH to 4.6 ± 0.05 with 0.1 M HCl / NaOH, then add DCC and NHS in the following ratio: HA repeating unit: DCC (N,N'-dicyclohexylcarbodiimide, the same below): NHS = 1:0.3:0.15 (molar ratio). Stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0046] Step S2: Dissolve cellulose acetate propionate in amyl acetate to form a solution with a concentration of 0.5 wt.%, which serves as the oil phase.

[0047] Step S3: Under mechanical stirring at 90 ℃ and 1500 rpm, 50 mL of aqueous phase was added to 50 mL of oil phase, and the mixture was suspended and polymerized for 0.5 h. After the reaction was completed, the microspheres were collected by centrifugation, dialyzed against the oil phase solvent and anhydrous ethanol in sequence, and dried to obtain the product.

[0048] Example 9: Step S1: Dissolve HA with a molecular weight of 150 kDa in physiological saline to form a solution with a concentration of 22 wt.%. Adjust the pH to 6.5 ± 0.05 with 0.5 M HCl / KOH, then add DIC and Sulfo-NHS in the following ratio: HA repeating unit: DIC (N,N'-diisopropylcarbodiimide, the same below): Sulfo-NHS (sodium N-hydroxythiosuccinimide, the same below) = 1:1:1.5 (molar ratio). Stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0049] Step S2: Dissolve polymethyl methacrylate in dimethyl carbonate to form a solution with a concentration of 15 wt.%, which serves as the oil phase.

[0050] Step S3: Under mechanical stirring at 40 ℃ and 200 rpm, 50 mL of aqueous phase was added to 2000 mL of oil phase, and the mixture was suspended and polymerized for 4 h. After the reaction was completed, the microspheres were collected by centrifugation, dialyzed against the oil phase solvent and anhydrous ethanol in sequence, and dried to obtain the product.

[0051] Example 10: Step S1: Dissolve HA with a molecular weight of 150 kDa in phosphate buffer to form a 5 wt.% solution. Adjust the pH to 6.9 ± 0.05 with 0.5 M phosphate / KOH, then add CMC and NHSS in the following ratio: HA repeating unit: CMC (N-cyclohexyl-N'-(2-morpholinoethyl)carbodiimide methanesulfonate, hereinafter the same): NHSS (N-hydroxysulfosuccinimide, hereinafter the same) = 1:1.5:2.25 (molar ratio). Stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0052] Step S2: Dissolve polyvinyl butyral in butyl butyrate to form a 12 wt.% solution as the oil phase.

[0053] Step S3: Under mechanical stirring at 60 ℃ and 650 rpm, 50 mL of aqueous phase was added to 1000 mL of oil phase, and the mixture was suspended and polymerized for 2 h. After the reaction was completed, the microspheres were collected by centrifugation, dialyzed against the oil phase solvent and anhydrous ethanol in sequence, and dried to obtain the product.

[0054] Comparative Example 1 (different from Example 1 in terms of HA concentration): Step S1: Dissolve HA with a molecular weight of 100 kDa in deionized water to form a solution with a concentration of 4 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:0.5:0.5 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0055] The other steps are the same as in Example 1.

[0056] Comparative Example 2 (the difference from Example 2 lies in the concentration of HA): Step S1: Dissolve HA with a molecular weight of 200 kDa in deionized water to form a solution with a concentration of 4 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:0.5:0.5 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0057] The other steps are the same as in Example 1.

[0058] Comparative Example 3 (different from Example 3 in that the concentration of HA is different): Step S1: Dissolve HA with a molecular weight of 500 kDa in deionized water to form a solution with a concentration of 2 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:0.5:0.5 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0059] The other steps are the same as in Example 1.

[0060] Comparative Example 4 (the difference from Example 4 is the ratio of HA repeating units to EDC and NHS): Step S1: Dissolve HA with a molecular weight of 100 kDa in deionized water to form a solution with a concentration of 10 wt.%. Adjust the pH to 4.8 ± 0.05 with 0.1 M HCl / NaOH, then add EDC and NHS according to the HA repeating unit: EDC: NHS = 1:0.2:0.2 (molar ratio), and stir at room temperature to obtain a homogeneous solution, which is used as the aqueous phase.

[0061] The other steps are the same as in Example 1.

[0062] II. Performance Testing 1. Microsphere Formability (1) Test sample The products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 of this invention.

[0063] (2) Test items Microscopic morphology: physiological saline was added to the sample to be tested and observed under a microscope.

[0064] (3) Test results As shown in Table 1, not all solutions of all concentrations can yield spherical products after suspension polymerization. Figure 1 (bottom left) shows the microstructure of the product of Example 1, which can be seen as fine, irregular particles. After reconstitution with physiological saline, the product of Example 1 swelled into spherical gel particles (Figure 1, top). However, the product of Comparative Example 1 was significantly different. Before swelling with physiological saline, its morphology was not significantly different from that of the product of Example 1; however, after the addition of physiological saline, it could not maintain the spherical particle shape and instead dissolved directly in the physiological saline to form flocculent floating matter (Figure 1, bottom right).

[0065] ; (4) Results Analysis The intermediate formed during the catalytic activation of carboxyl groups by carbodiimide derivatives and N-hydroxysuccinimide derivatives is highly reactive and can be consumed by hydroxyl groups in water. In other words, the hydroxyl groups in HA and the hydroxyl groups in the aqueous solution compete with the activated carboxyl groups in HA for reaction. When the concentration of HA in the reaction system is sufficiently low, the number of cross-links formed is insufficient, i.e., the degree of cross-linking is inadequate. Therefore, the resulting cross-linked gel particles cannot withstand the swelling effect of water molecules and break down, losing their spherical shape.

[0066] The products obtained in Examples 2-10 have similar sphericity to the product obtained in Example 1.

[0067] 2. Degree of cross-linking and related properties (1) Test sample The products prepared in Examples 1, 4, 6, 7 and Comparative Example 4 of this invention.

[0068] (2) Test items Swelling degree: Weigh the sample to be tested, and record the mass as m1. Add the product to sufficient physiological saline to fully swell, remove the swollen gel, wipe off the free water on the surface, and weigh it, recording the mass as m2. The swelling degree is (m2-m1) / m1.

[0069] Storage modulus: The sample to be tested was added to sufficient physiological saline to fully swell and remove free water from the gel microspheres. The gel microspheres were placed on the flat rotor of the rheometer, the experimental temperature was 25℃, the constant strain was 1%, the thickness was 1 mm, and the result was recorded at 0.1 Hz on a 25 mm flat rotor.

[0070] Hydrolysis: The sample to be tested was added to a sufficient amount of physiological saline to fully swell, and then placed at 70℃ to accelerate hydrolysis. Observation was performed every 0.5 hours, and the hydrolysis endpoint was defined as the absence of gel-like particles in the solution.

[0071] Enzymatic hydrolysis: Take 50 mg of the sample to be tested and add 5 mL of 50 U / mL sodium hyaluronate enzyme saline solution. After shaking well, incubate at 37℃ for enzymatic hydrolysis. Observe every 1 h, and take the point at which no gel-like particles can be observed under a microscope as the end point of enzymatic hydrolysis.

[0072] Pushing force: Add sufficient physiological saline to the sample to be tested for reconstitution, draw the reconstituted gel microspheres into a 1 mL syringe, let stand, and then push out the free water. Use a 27G needle and set the pushing speed to 30 mm / min.

[0073] (3) Test results As shown in Table 2, the cross-linked HA gel microspheres with different catalyst dosages exhibit significant performance characteristics.

[0074] ; (4) Results Analysis Crosslinking density and mechanical properties: As the molar ratio of HA repeating unit: EDC: NHS increased from 1:0.3:0.3 (Example 4) to 1:1.5:1.5 (Example 7), the swelling degree decreased from 70.9 to 12.5, and the storage modulus increased from 58 Pa to 3410 Pa (e.g., ...). Figure 2 As shown in the figure, the modulus was increased by approximately 59 times, demonstrating that the ester bond crosslinking network can achieve gradient "high modulus" control without the need for external crosslinking agents. The swelling degree of the products obtained in Examples 1-10 was in the range of 12.5-70.9.

[0075] The degradation rate and cross-linking degree are weakly coupled: the hydrolysis time only increased from 4 h to 11 h (less than 3 times), and the enzymatic hydrolysis time increased from 5 h to 74 h (about 15 times), both significantly lower than the increase in modulus (59 times). This "weak coupling" phenomenon verifies the core effect of the present invention of "achieving both high modulus and rapid degradation". The mechanism is that: ester bonds are "easily hydrolyzed bonds", water molecules can penetrate the entire microsphere network and break simultaneously, rather than surface-centripetal layer-by-layer degradation. Even with a significant increase in cross-linking degree, the overall hydrolysis time is still short; the enzymatic hydrolysis time is not the rate-determining step of the overall degradation of the material.

[0076] Injectability: The maximum pushing force of the spherical samples is ≤ 5 N, which is far lower than the "comfortable injection" threshold (about 10 N) of the commonly used 27 G needle in clinical practice. Moreover, the pushing force does not increase significantly with the increase of cross-linking degree, which confirms that the rounded microspheres still maintain the advantage of "low rolling resistance" in the "high modulus" state.

[0077] Critical crosslinking degree: The crosslinking density of the gel formed by Comparative Example 4 (molar ratio 1:0.2:0.2) was too low, and it still had strong fluidity, making it impossible to test mechanical and degradation properties. This further confirms that a sufficient level of crosslinking is a necessary condition to ensure spherical gel particles, which is consistent with the conclusion of "microsphere formation".

[0078] 3. Infrared spectroscopy (1) Test sample The product prepared in Example 7.

[0079] (2) Test items According to the Chinese Pharmacopoeia (2020 Edition), Part IV, 0402, infrared spectrophotometry method, the results were obtained.

[0080] (3) Test results Example 7 and the infrared spectrum of the raw materials used are shown below. Figure 3 As shown.

[0081] (4) Results Analysis Since the infrared characteristics of the products prepared in each example are almost identical, the spectrum of Example 7 (high crosslinking level) was used as the representative spectrum for analysis.

[0082] Sodium hyaluronate (HA) is a polysaccharide whose main infrared characteristic peaks include: approximately 3400 cm⁻¹ -1 OH stretching vibration (hydroxyl group); approximately 2900 cm⁻¹ -1 CH stretching vibration (methylene and methine groups on the sugar ring). Approximately 1650 cm⁻¹ -1 Approximately 1550cm -1 The peaks are amide I and amide II bands (derived from N-acetylglucosamine units). These peaks can be observed in both the HA raw material and the gel microspheres. Furthermore, the infrared peak shapes of the HA raw material and the gel microspheres are essentially the same, indicating that the gel microspheres are almost entirely composed of HA.

[0083] However, compared to gel microspheres, some typical characteristic peaks of HA raw materials have changed. For example, the peak at approximately 1600 cm⁻¹... -1 Approximately 1410 cm -1 (Labeled as #1 and #2 in the figure): The asymmetric and symmetric stretching vibrations of carboxylic acids show a significant decrease in relative peak intensity in the gel microspheres, indicating that the number of carboxyl groups in the gel microspheres is reduced compared to the HA raw material; approximately 1100-1000 cm⁻¹ -1 (Labeled as #3 in the figure): Both COC and CO stretching vibrations (glycosidic bonds and hydroxyl groups) showed a decrease in relative peak intensity in the gel microspheres, indicating a reduction in the number of carboxyl groups compared to the HA raw material. Furthermore, compared to the HA raw material, the gel microspheres exhibited a lower peak intensity at approximately 1700 cm⁻¹. -1A new characteristic peak has been added at position #4 in the figure. This peak is attributed to the stretching vibration peak of the carbonyl group on the ester bond.

[0084] The changes in the intensity of the infrared peaks and the addition of new peaks indicate that the composition of the gel microspheres remains HA. After cross-linking, the amount of carboxyl and hydroxyl groups decreases, and ester bonds are formed.

[0085] In summary, this indicates that the gel microspheres are formed through self-crosslinking of ester bonds.

[0086] 4. Microsphere particle size (1) Test sample The products prepared in Examples 7 to 10 of this invention.

[0087] (2) Test items Particle size: After swelling in physiological saline to reach steady state, the particle size was determined by wet method according to the third method (light scattering method) of particle size and particle size distribution determination in the Pharmacopoeia of the People's Republic of China (Part IV) (2020 Edition) 0982.

[0088] (3) Test results The particle size distribution diagrams of the products prepared in Examples 7-10 are shown below. Figure 4 As shown in Table 3, the particle size statistics are as follows.

[0089] ; (4) Results Analysis The particle size distribution of gel microspheres can be controlled by parameters such as molecular weight concentration and water-oil ratio, and microspheres with sizes ranging from 2.8 to 2000 μm can be prepared. Sieving the product can also yield products with narrower particle size distributions. The particle sizes of the products obtained in Examples 1-10 are all in the range of 2.8 to 2000 μm.

[0090] In summary: 1. The sodium hyaluronate gel microspheres provided by the present invention are formed by the self-crosslinking of hyaluronic acid, and there will be no carbodiimide derivatives or N-hydroxysuccinimide derivatives connected to sodium hyaluronate by chemical bonds in the product, thus reducing the risk of adverse reactions. 2. The hyaluronic acid in the sodium hyaluronate gel microspheres provided by the present invention is cross-linked through ester bonds. The gel modulus is significantly increased due to the increase in the degree of cross-linking, while the degradation cycle changes little. Thus, it can take into account both high modulus and fast degradation, and is particularly suitable as a short-term rigid filler material. 3. Compared with existing technologies (such as CN 111647193 A for obtaining sponge-like sodium hyaluronate gel), the preparation method of the present invention can obtain spherical sodium hyaluronate gel products through suspension polymerization. The rolling resistance between spherical particles is small, making it easy to inject and use.

[0091] The purpose of the above embodiments is to specifically illustrate the substantive content of the present invention, but those skilled in the art should know that the scope of protection of the present invention should not be limited to the specific embodiments.

Claims

1. A sodium hyaluronate gel microsphere, characterized in that: The sodium hyaluronate gel microspheres are formed by self-crosslinking of hyaluronic acid, and the crosslinking bonds are ester bonds; the swelling degree of the sodium hyaluronate gel microspheres ranges from 12.5 to 70.9, and the particle size ranges from 2.8 to 2000 μm; The sodium hyaluronate gel microspheres were prepared by a method including the following steps: Step S1: Dissolve hyaluronic acid or its salt and the catalyst in solvent A to obtain an aqueous solution; Step S2: Dissolve the thickener in solvent B to obtain an oil phase solution; Step S3: Mix the aqueous solution and the oil solution, and carry out suspension polymerization. The product is obtained after the reaction is completed. in: In step S1, the catalyst is composed of a carbodiimide derivative and an N-hydroxysuccinimide derivative; a repeating unit is defined as a group of glucuronic acid and acetylglucosamine in hyaluronic acid or its salts, and the molar ratio of the repeating unit in hyaluronic acid or its salts to the carbodiimide derivative and the N-hydroxysuccinimide derivative is 1:(0.3~1.5):(0.15~2.25); the solvent A is selected from one or more of water, physiological saline, and phosphate buffer; the molecular weight of the hyaluronic acid or its salts is 40 kDa~1000 kDa, and its concentration in the aqueous solution is 5~22 wt.%. In step S2, the thickener is selected from one or more of cellulose acetate butyrate, cellulose acetate propionate, polymethyl methacrylate, and polyvinyl butyral; the solvent B is selected from one or more of butyl acetate, amyl acetate, dimethyl carbonate, and butyl butyrate.

2. The sodium hyaluronate gel microspheres according to claim 1, characterized in that: In step S1, the carbodiimide derivative is selected from one or more of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N,N'-dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide, and N-cyclohexyl-N'-(2-morpholinoethyl)carbodiimide methanesulfonate.

3. The sodium hyaluronate gel microspheres according to claim 1, characterized in that: In step S1, the N-hydroxysuccinimide derivative is selected from one or more of N-hydroxysuccinimide, sodium N-hydroxythiosuccinimide, and N-hydroxysulfosuccinimide.

4. The sodium hyaluronate gel microspheres according to claim 1, characterized in that: In step S1, the pH range of the aqueous solution is 4.55 to 6.

95.

5. The sodium hyaluronate gel microspheres according to claim 1, characterized in that: In step S2, the concentration of the thickener in the oil phase solution is 0.5 ~ 15 wt.%.

6. The sodium hyaluronate gel microspheres according to claim 1, characterized in that: In step S3, the volume ratio of the aqueous phase solution to the oil phase solution is 1:1 to 40.

7. The sodium hyaluronate gel microspheres according to claim 1, characterized in that: In step S3, the temperature of suspension polymerization is 10 ~ 90℃, the reaction time is 0.5 ~ 24 h, and the stirring speed is 200 ~ 1500 rpm.

8. The use of sodium hyaluronate gel microspheres according to any one of claims 1 to 7 in the preparation of medical filler materials.

Citation Information

Patent Citations

  • Preparation method of porous gelatin / hyaluronic acid composite microspheres

    CN103816573A

  • Method for improving self-crosslinking degree of hyaluronic acid and hyaluronic acid self-crosslinking product

    CN111647193A

  • Self-crosslinking hyaluronic acid microsphere without exogenous crosslinking agent and preparation method of self-crosslinking hyaluronic acid microsphere

    CN121059898A